If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + 25) * 2x = 180 Reorder the terms: (25 + 3x) * 2x = 180 Reorder the terms for easier multiplication: 2x(25 + 3x) = 180 (25 * 2x + 3x * 2x) = 180 (50x + 6x2) = 180 Solving 50x + 6x2 = 180 Solving for variable 'x'. Reorder the terms: -180 + 50x + 6x2 = 180 + -180 Combine like terms: 180 + -180 = 0 -180 + 50x + 6x2 = 0 Factor out the Greatest Common Factor (GCF), '2'. 2(-90 + 25x + 3x2) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-90 + 25x + 3x2)' equal to zero and attempt to solve: Simplifying -90 + 25x + 3x2 = 0 Solving -90 + 25x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -30 + 8.333333333x + x2 = 0 Move the constant term to the right: Add '30' to each side of the equation. -30 + 8.333333333x + 30 + x2 = 0 + 30 Reorder the terms: -30 + 30 + 8.333333333x + x2 = 0 + 30 Combine like terms: -30 + 30 = 0 0 + 8.333333333x + x2 = 0 + 30 8.333333333x + x2 = 0 + 30 Combine like terms: 0 + 30 = 30 8.333333333x + x2 = 30 The x term is 8.333333333x. Take half its coefficient (4.166666667). Square it (17.36111111) and add it to both sides. Add '17.36111111' to each side of the equation. 8.333333333x + 17.36111111 + x2 = 30 + 17.36111111 Reorder the terms: 17.36111111 + 8.333333333x + x2 = 30 + 17.36111111 Combine like terms: 30 + 17.36111111 = 47.36111111 17.36111111 + 8.333333333x + x2 = 47.36111111 Factor a perfect square on the left side: (x + 4.166666667)(x + 4.166666667) = 47.36111111 Calculate the square root of the right side: 6.881940941 Break this problem into two subproblems by setting (x + 4.166666667) equal to 6.881940941 and -6.881940941.Subproblem 1
x + 4.166666667 = 6.881940941 Simplifying x + 4.166666667 = 6.881940941 Reorder the terms: 4.166666667 + x = 6.881940941 Solving 4.166666667 + x = 6.881940941 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.166666667' to each side of the equation. 4.166666667 + -4.166666667 + x = 6.881940941 + -4.166666667 Combine like terms: 4.166666667 + -4.166666667 = 0.000000000 0.000000000 + x = 6.881940941 + -4.166666667 x = 6.881940941 + -4.166666667 Combine like terms: 6.881940941 + -4.166666667 = 2.715274274 x = 2.715274274 Simplifying x = 2.715274274Subproblem 2
x + 4.166666667 = -6.881940941 Simplifying x + 4.166666667 = -6.881940941 Reorder the terms: 4.166666667 + x = -6.881940941 Solving 4.166666667 + x = -6.881940941 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4.166666667' to each side of the equation. 4.166666667 + -4.166666667 + x = -6.881940941 + -4.166666667 Combine like terms: 4.166666667 + -4.166666667 = 0.000000000 0.000000000 + x = -6.881940941 + -4.166666667 x = -6.881940941 + -4.166666667 Combine like terms: -6.881940941 + -4.166666667 = -11.048607608 x = -11.048607608 Simplifying x = -11.048607608Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.715274274, -11.048607608}Solution
x = {2.715274274, -11.048607608}
| 3x+7y=-12 | | -n+10-2n=-5(n+2) | | 60x/600 | | 2=a-6+3a | | A=D-B-C | | 9x-3(2-x)=4(3x+8)-7x | | x^2=0.11-1.8x | | (6x+11+9x)= | | r+7-1=6 | | 0.7=x-1.2x | | b/5-9=-1 | | 9000=.07*1*x | | 43=-7+5x | | 3ln(3x-4x^3)=0 | | X+2y=195 | | x*y=24 | | 2.8=ln(y) | | 9000=.05*1*x | | 6x-6x+9=9 | | 15=1+6a+a | | 15x+5=135 | | 1+5p+8p=1 | | x+y=39 | | 6r-5r=-7 | | 1x+2y=49 | | -9=c/12 | | 98=6+34 | | 5=7v+8+4 | | Ln(8x+2)=Ln(4x-10) | | 50/5= | | 12x+5x+7=9 | | -6=k-8-1 |